Experimental and Numerical Modeling of Fluid Flow - Schwarze, Rüdiger (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue provides an overview of the applied experimental and numerical flow, models, which are used to investigate fluid flow in complex situations. The investigated problems are related to fundamental processes or new applications. As demonstrated, the field of the application of experimental and numerical flow models is constantly expanding.